Is local always best? Social acceptance of small hydropower projects in Norway. - Rygg, Bente Johnsen; Ryghaug, Marianne; Yttri, Gunnar (International Journal of Sustainable Energy Planning and Management, 2021)
Small-scale development of renewable energy has been identified as one possible solution to meet future energy needs and is well aligned with the general European trend towards further development of community energy projects. Increased local energy production will move energy plants closer to habitation, placing aspects related to social acceptance at the center stage [1, 2]. Until recently, small hydro power [3] projects in Norway have been owned by local farmers and others with property rights to rivers. As the profitability of these projects has decreased, international investors have taken interest in SHP projects as part of their long-term investment strategy. In this paper, we study what influences social acceptance of SHP projects in Norway based on interviews and qualitative data from different SHP projects in Norway. We find that community energy projects often are attributed positive qualities when ownership is local. Thus, we argue that there is a need to consider more thoroughly how to organize ownership of small-scale renewables in the future, if it is to uphold its position as a popular and viable solution to meet future energy needs [3].